FOREIGN EXPERIENCES IN PERSONAL SOCIALIZATION OF STUDENTS THROUGH LIBRARIES - Muminova Dilafro‘z Akbaraliyevna (The Bioscan, 2025)
This article provides an analysis of foreign experiences in the personal socialization of students through reading, the positive aspects of reading, becoming a librarian, the opinions of world scientists about reading, and information about their work. KEYWORDS reading, young generation, program, students, work, text, author, research, reading, communication, literacy, education, foreign experiences, students, works, reading.